2019
DOI: 10.1039/c8ra08984a
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional property exploration: Bi4O5I2 with high visible light photocatalytic performance and a large nonlinear optical effect

Abstract: Bi4O5I2 exhibits an extremely high second harmonic generation response and enhanced photocatalytic activity. The multifunction of Bi4O5I2 is mainly resulting from the dipole moment of the stereochemical activity of Bi 6s lone pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The Kubelka–Munk transformation and Tauc method were introduced to estimate the energy gap of Sb 5 O 7 I. The result suggests a direct energy gap of 3.22 eV, compatible with the crystals’ transparent color (Figure a), which is far higher than the energy gaps of other metal oxyhalides, like CuSb 2 O 3 Cl (2.74 eV), CuSb 2 O 3 Cl (2.64 eV), Sb 3 O 4 I (2.16 eV), Sb 8 O 11 I 2 (2.74 eV), BiOI (1.83 eV), and Bi 4 O 5 I 2 (2.39 eV) . To our knowledge, Sb 5 O 7 I has the largest energy gap of all reported ternary oxyiodides (Table S6).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The Kubelka–Munk transformation and Tauc method were introduced to estimate the energy gap of Sb 5 O 7 I. The result suggests a direct energy gap of 3.22 eV, compatible with the crystals’ transparent color (Figure a), which is far higher than the energy gaps of other metal oxyhalides, like CuSb 2 O 3 Cl (2.74 eV), CuSb 2 O 3 Cl (2.64 eV), Sb 3 O 4 I (2.16 eV), Sb 8 O 11 I 2 (2.74 eV), BiOI (1.83 eV), and Bi 4 O 5 I 2 (2.39 eV) . To our knowledge, Sb 5 O 7 I has the largest energy gap of all reported ternary oxyiodides (Table S6).…”
mentioning
confidence: 83%
“…It can be noted that most of these oxyhalides are fluorides, chlorides, and bromides, while iodides are very rare because of their synthetic difficulties. In addition, oxyhalides containing lone-pair cations or d 0 transition-metal cations may increase the possibility for obtaining noncentrosymmetric (NCS) structures because of their second-order Jahn–Teller effects. However, most metal oxyhalides are crystallized with centrosymmetric (CS) structures because of the antiparallel arrangement of their asymmetric units .…”
mentioning
confidence: 99%
“…35 Yin et al, Hou et al and Xiao et al have reported nanostructured Bi 4 O 5 I 2 successively including nano-akes and nano-roses fabricated via a complicated organic solvent method. [36][37][38] To the best of our knowledge, there has been no report on the synthesis and application of porous Bi 4 O 5 I 2 nanosheets. Herein, we prepared novel mesoporous Bi 4 O 5 I 2 single-crystal nanosheets using a simple one-step method.…”
Section: Introductionmentioning
confidence: 99%
“…Pure Bi 4 O 5 I 2 nanosheets were prepared by a solvothermal method, based on the previous report [ 32 ]. Typically, 5 mmol Bi(NO 3 ) 3 ∙5H 2 O and 10 mmol KI powders were dissolved into 80-mL ethylene glycol under continuous stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%